2000
DOI: 10.1093/carcin/21.11.2057
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of partial and extensive methylation at the p14ARF locus with reduced mRNA expression in colorectal cancer cell lines and clinicopathological features in primary tumors

Abstract: p14(ARF) is a putative tumor suppressor gene thought to modify the levels of p53. CpG sites within the 5'-flanking region and exon 1beta of p14(ARF) are targets of aberrant methylation and transcriptional silencing in human colorectal cancer (CRC). Here we have developed methylation-specific polymerase chain reaction (MSPCR) methods to detect methylation of CpG sites in p14(ARF) in CRC cell lines and primary CRC tumors, and correlated p14(ARF) mRNA expression with methylation in CRC cell lines using competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
56
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 16 publications
9
56
1
Order By: Relevance
“…This appears at odds with the data presented herein. However, the authors also report that SW480 colorectal cancer cells with (Myohanen et al, 1998); HCT15 cells are reported to carry a 'high-density of methylation' at p16 INK4a as observed (Zheng et al, 2000). HCT15 cells that express high levels of ascl2 showed evidence for unmethylated DNA only.…”
Section: Discussionmentioning
confidence: 87%
“…This appears at odds with the data presented herein. However, the authors also report that SW480 colorectal cancer cells with (Myohanen et al, 1998); HCT15 cells are reported to carry a 'high-density of methylation' at p16 INK4a as observed (Zheng et al, 2000). HCT15 cells that express high levels of ascl2 showed evidence for unmethylated DNA only.…”
Section: Discussionmentioning
confidence: 87%
“…Zheng et al (2001) reported previously that the partial methylation pattern was associated with relatively low levels of p14ARF in colorectal cancer cell lines. p14ARF mRNA was expressed at extremely low levels in fully methylated cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…Zheng et al (2000) reported previously that a partial methylation pattern was associated with relatively low levels of p14ARF in colorectal cancer cell lines. p14ARF mRNA was expressed at extremely low levels in fully methylated cell lines, and p14ARF expression in the partial methylated LoVo cell line was intermediate.…”
Section: Discussionmentioning
confidence: 91%